The riquier problem for a nonlinear equation unresolved with respect to the Lévy iterated laplacian - Feller, M. N. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We present a method of solving for the nonlinear equationf(U(x),Δ L 2 U(x)) = Δ L U(x) (Δ L is an infinite-dimensional Laplacian) unresolved with respect to an iterated infinite-dimensional Laplacian and for the Riquier problem for this equation.